I'jaz Tikrari in the Qur'an Surah Al-Muddatssir and Surah Al-Mursalat Study of Balaghah Science Analysis - Hidayat, Abdul Yahya; Ahmad Zuhri; Muhammad Hdayat; Sitanggang, Cokro Malik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The existence of tikrar in the Qur'ān is a frequent attack by Orientalists. In the Qur'an there are verses that outwardly appear to be repetitions, but they are not actually repetitions because the context of the link or target of the verse that appears to be repeated is not the same. One of them is in surah Al-Muddatssir in which there is a repetition of the word Qaddar 3 times and surah Al-Mursalat in which there is a repetition of verses 10 times, namely in the sentence Wayluy Yaumaizin Lil Mukazzibin.The research in this thesis discusses I'jaz Tikrari in the Qur'an surah Al-Muddatssir and surah Al-Mursalat, to study and prove the I'jaz of the Qur'an. The miracle of the Qur'an (I'jaz Al-Qur'an) has been agreed upon by scholars, both from scientific, legal and linguistic aspects. The miraculousness of the Qur'an linguistically is often criticised by orientalists, especially in relation to the Tikrar (repetition) of verses in the Qur'an which considers that Tikrar in the Qur'an is a defect and irregularity. This study aims to answer the criticism of the Qur'an that the existence of Tikrar in it causes the Qur'an to lose its existence as I'jaz. The type of research used is (library research) by making the Qur'an, Tafsir and Lughah books as the main sources. As for the results of this thesis research, that the repetition of verses in surah Al-Muddatssir and surah Al-Mursalat, does not cause these two surahs to be defective, but rather the Tikrar in these two surahs is proof of the Qur'an's I'jaz which is very deep in the choice of diction of each verse.